Comprehensive Evaluation Method for the Grouting Management Effect of Mine Water Hazards Based on the Combined Assignment of the TOPSIS and RSR Methods - Shuangcheng Tang; Xuehai Fu; Baolei Xie (Applied Sciences)
The effectiveness of grouting management is closely linked to the safety of mining operations, making the scientific and accurate evaluation of mine water hazard grouting management a critical issue that demands immediate attention. Current evaluation technologies for grouting effectiveness are limited by singularity in indicator assignment, reliance on isolated indicators, and the generalization of weak metrics. Using the top and bottom grouting project of the 110504 working face at the Banji coal mine in Anhui Province as a case study, both theoretical and practical insights were integrated. Drilling fluid consumption, final grouting pressure, water permeability, and dry material per unit length were selected as key indicators to establish a comprehensive grouting effect evaluation index system. To address the limitations of previous assignment methods, this study proposes a novel approach that combines the Precedence Chart (PC) with the Criteria Importance Through Intercriteria Correlation (CRITIC) method. This integrated approach resolves the issues of singularity and subjectivity in prior assignment techniques. The evaluation system was constructed based on a single indicator framework, incorporating a comprehensive evaluation model that uses the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) for ranking and the Rank Sum Ratio (RSR) for classification support. The model demonstrates a high goodness-of-fit, with a value of 0.938, indicating strong performance. The model’s results were visualized in the form of a grouting effect zoning map, further validated through comparisons with actual on-site water discharge data and exploration borehole water inflow measurements. A maximum recorded influx of 70 m3/h, aligning with the relatively weak grouting zones identified in the evaluation. The findings demonstrate that the proposed model exhibits a high degree of reliability and scientific rigor, providing valuable theoretical guidance for enhancing coal body stability and minimizing coal loss.